2018
DOI: 10.1080/13696998.2018.1539400
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of secukinumab in ankylosing spondylitis from the Canadian perspective

Abstract: Aim: To assess the cost-effectiveness of interleukin (IL)-17A inhibitor secukinumab vs the currently licensed biologic therapies in ankylosing spondylitis (AS) patients from a Canadian healthcare system perspective. Methods: A decision analytic model (semi-Markov) evaluated the cost-effectiveness of secukinumab 150 mg compared to certolizumab pegol, adalimumab, golimumab, etanercept and etanercept biosimilar, and infliximab and infliximab biosimilar in a biologic-naïve population, over 60 years of time horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…This is among the first full-length studies assessing cost-effectiveness of secukinumab 150 mg compared with other biologics. However, other modeling studies have been conducted in different countries such as Canada,34 UK,35,36 Turkey,37 Colombia,38 Bulgaria,39 and Russia;40 which reported similar results. All these studies reported secukinumab to be dominant (more effective and less costly) over anti-TNFs in biologic-naïve as well as biologic-experienced AS population.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This is among the first full-length studies assessing cost-effectiveness of secukinumab 150 mg compared with other biologics. However, other modeling studies have been conducted in different countries such as Canada,34 UK,35,36 Turkey,37 Colombia,38 Bulgaria,39 and Russia;40 which reported similar results. All these studies reported secukinumab to be dominant (more effective and less costly) over anti-TNFs in biologic-naïve as well as biologic-experienced AS population.…”
Section: Discussionmentioning
confidence: 62%
“…All these studies reported secukinumab to be dominant (more effective and less costly) over anti-TNFs in biologic-naïve as well as biologic-experienced AS population. Across multiple studies, secukinumab resulted in an additional 0.20–0.86 QALY gain at a total cost, which was €4,644 to €9,134 lower compared with other biologics 34,37,38. The current study is also the first to assess cost-effectiveness of secukinumab in a Finnish context.…”
Section: Discussionmentioning
confidence: 78%
“…According to reimbursement guidelines of Korea, secukinumab is classified as a secondary biologic agent to be used in AS patients who had inadequate response or adverse reactions to TNFis. As shown in Table , an economic analysis documented cost‐effectiveness of secukinumab in biologic‐naïve patients with AS in various countries . However, applying 1 country's results to another is not appropriate due to the differences in terms of healthcare systems and healthcare cost in each country.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 3, an economic analysis documented cost-effectiveness of secukinumab in biologic-naïve patients with AS in various countries. [18][19][20][21][22][23][24] However, applying 1 country's results to another is not appropriate due to the differences in terms of healthcare systems and healthcare cost in each country. Therefore, we analyzed the cost per responder of secukinumab from the Korean perspective based on the ASAS according to Korean healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation